Role of tertiary care institutions for preventive activities for positive health: an exploratory study among defence and civilian health care facilities of Bangalore - M. R., Subodh; V., Narendranath; B. S., Nanda Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Health sector in India is facing several challenges. These can be attributed to population, poverty, illiteracy, poor social indices, poor patient to hospital ratio and inadequate government spending. Preventive activities for positive health by the various tertiary care institutions play a crucial role in mitigating some of the problems. The study was undertaken to assess the preventive services for positive health among tertiary care institutions of defence and civilian HCFs in Bangalore. Methods: Study was conducted by interacting with the key respondents of defence, government and private tertiary care hospitals. Using structured checklist, activities pertaining to preventive services promoting positive health was assessed. Results: Study shows that preventive health activities are being undertaken in all the sectors. There is varying degrees of effectiveness of implementation of the programs. Defence sector has maximised the service delivery and coverage, while Government sector delivers the preventive services through its outreach and national program implementation drive. In case of Private sector, though the focus is largely on curative care, preventive health services are being undertaken in a fragmented manner. Conclusions: Preventive activities for positive health can be optimally utilized and implemented by having coordination and cross-sectorial linkages of services. All the teaching hospitals and government hospitals may undertake these programs in a more systematic manner. Sharing of experiences and research between sectors in optimum provision of preventive services, may help in curtailing the increasingly expensive healthcare costs and improve the health of the communities.